1980
DOI: 10.1104/pp.65.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Cytokinin Antagonists 7-(Pentylamino) and 7-(Benzylamino)-3-Methylpyrazolo(4,3-d)Pyrimidines on Suspension-cultured Tobacco Cells

Abstract: We have studied the biological effects of two structural analogs of cytokinins, 3-methyl-7-(pentylamino)pyrazolo(4,3-d)pyimiine and 3-methyl-7-(benzylamino)pyrazolo(4,3d)pyrimidine, on tobacco cell suspension cultures. These two cytokinin analogs are highly inhibitory to cytokinin-autonomous and cytokinin-requiring tobacco cells. The growth inhibitory effect is markedly antagonized by benzyladenine, but not by adenine.Cell suspensions of tobacco cells of a cytokinin-autonomous strain become cytokinin-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Abnormalities of the mitotic apparatus induced by ANCYT1 treatment could result from its inhibitory effect on CDKs and probably other related kinases that have functions during mitosis. The results are also in good agreement with the findings of Gregorini and Laloue (47), who previously demonstrated that in both cytokinin-requiring and cytokinin-autonomous tobacco cell suspension culture, only dividing cells are sensitive to the cytotoxic effects of ANCYT1.…”
Section: Discussionsupporting
confidence: 81%
“…Abnormalities of the mitotic apparatus induced by ANCYT1 treatment could result from its inhibitory effect on CDKs and probably other related kinases that have functions during mitosis. The results are also in good agreement with the findings of Gregorini and Laloue (47), who previously demonstrated that in both cytokinin-requiring and cytokinin-autonomous tobacco cell suspension culture, only dividing cells are sensitive to the cytotoxic effects of ANCYT1.…”
Section: Discussionsupporting
confidence: 81%
“…RD 21, which is ineffective in most biological assays (23), inhibits the alternative pathway more strongly than kinetin. Moreover, 7 PMP, an anticytokinin (9), is the most powerful inhibitor of the cyanideresistant electron transfer. Finally, it should be mentioned that zeatin, a naturally occurring cytokinin, has almost no effect on the alternative pathway (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…According to the model of Mohr and Schopfer [17], the light response and the cytokinin response are the results of independent series of events . After other experimental results [3,4,13] it was suggested that the light effect(s) and the cytokinin effect(s) might interact : in favour of this hypothesis it was mentioned previously that PAMPP (7-(pentylamino)-3-methylpyrazolo (4,3-d-pyrimidine), a well known competitive anticytokinin [10,20] inhibited the stimulating effect of white light on amaranthin synthesis as well as the cytokinin response [3] .…”
Section: Introductionmentioning
confidence: 99%